Media Pembelajaran Menggunakan Teknologi Augmented Reality untuk Tanaman Daun Herbal - Ayu Latifah; Dewi Tresnawati; Hariyana Sanjaya; Risa Aisyah (Jurnal Algoritma, 2022)
Herbal leaf plants have the potential to become an alternative treatment and increase national economic competitiveness because Indonesia is a country that has high biodiversity. Getting to know herbal leaf plants is one of the learning materials given to elementary school children in Natural Sciences subjects. Along with the times, the media for conveying information continues to experience development from time to time, starting with using books, direct learning in the field, educational videos and other recent technologies that have recently been proposed, one of which is Augmented Reality. With the development of this Augmented Reality technology, research was conducted aimed at building an interactive learning media for getting to know herbal leaf plants for grade 4 elementary school students as teaching aids in the classroom in understanding the content of existing material. By making this research, it is hoped able to increase students' interest in studying herbal leaf plants found around their environment. The research was conducted using the Research & Development methodology which consisted of the stages of potential and problem analysis, data collection, product design, design validation, design revision, product trials, product revisions, usage trials, product results and product publications. The results of this study are in the form of application products that are used as learning media for the introduction of herbal leaf plants for elementary school students which are packaged into the form of an Android platform to operate them.